Dynamic road pricing optimization with heterogeneous users - Dusica Joksimovic; Michiel Bliemer; Piet Bovy (European Regional Science Association (ERSA), 2005)
In transport networks, travelers individually make route and departure time choice decisions that may not be optimal for the whole network. By introducing (time-dependent) tolls the network performance may be optimized. In the paper, the effects of time-dependent tolls on the network performance will be analyzed using a dynamic traffic model. The network design problem is formulated as a bi-level optimization problem in which the upper level describes the network performance with chosen toll levels while the lower level describes the dynamic network model including user-specific route and departure time choice and the dynamic network loading. In case studies on a simple hypothetical network it is shown that network improvements can be obtained by introducing tolls. It is also shown that finding a global solution to the toll design problem is complex as it is non-linear and non-convex.
Keywords: 330